The electronic silk road how the web binds the world in commerce - Chander, Anupam (Yale University Press, 2013)
On the ancient Silk Road, treasure-laden caravans made their arduous way through deserts and mountain passes, establishing trade between Asia and the civilizations of Europe and the Mediterranean. Today's electronic Silk Roads ferry information across continents, enabling individuals and corporations anywhere to provide or receive services withoutobtaining a visa. But the legal infrastructure for such trade is yet rudimentary and uncertain. If an event in cyberspace occurs at once everywhere and nowhere, what law applies? How can consumers be protected when engaging with companies across the world?In this accessible book, cyber-law expert Anupam Chander provides the first thorough discussion of the law that relates to global Internet commerce. Addressing up-to-the-minute examples, such as Google's struggles with China, the Pirate Bay's skirmishes with Hollywood, and the outsourcing of services to India, the author insightfully analyzes the difficulties of regulating Internet trade. Chander then lays out a framework for future policies, showing how countries can dismantle barriers while still protecting consumer interests